2022
DOI: 10.29048/makufebed.1151024
|View full text |Cite
|
Sign up to set email alerts
|

Dış Mekân Termal Konfor Koşullarının Zamansal ve Mekânsal Dağılımı: Konyaaltı-Antalya Örneği

Abstract: Kentlerdeki dış mekân termal konfor, kentsel ortamlarda artan sıcaklıklar ile daha çok önem kazanmaya başlamıştır. Çalışmada Antalya ili Konyaaltı ilçesinin dış mekân termal konfor koşullarının zamansal ve mekansal dağılımının belirlenmesi amaçlanmıştır. Bu amaç doğrultusunda ilk olarak Konyaaltı ilçesi ve yakın çevresindeki meteoroloji gözlem istasyonlarından iklim verileri (sıcaklık, nem, rüzgâr hızı ve bulutluluk) elde edildi. Çalışmada dış mekân termal konfor koşulları, iklim parametrelerinin yanı sıra ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In other words, it assumes that the measured value closest to the prediction location has a greater influence than those farther away when making predictions. Consequently, as this method assigns more weight to points closer to the prediction location compared to those farther away, it is called the "Inverse Distance Weighted Method" (Watson, 1985;Karakuş and Selim, 2022). The formula for the Inverse Distance Weighted Method is expressed as:…”
Section: Methodsmentioning
confidence: 99%
“…In other words, it assumes that the measured value closest to the prediction location has a greater influence than those farther away when making predictions. Consequently, as this method assigns more weight to points closer to the prediction location compared to those farther away, it is called the "Inverse Distance Weighted Method" (Watson, 1985;Karakuş and Selim, 2022). The formula for the Inverse Distance Weighted Method is expressed as:…”
Section: Methodsmentioning
confidence: 99%
“…In terms of selecting the green areas, their central location in the city, areal sizes, vegetation densities, and environmental land uses were taken into consideration. Olgyay (1973) suggested that thermal comfort conditions deteriorate the most from May to October due to hot stress in the Mediterranean Climate Zone (Karakuş and Selim, 2022;Cinar et al, 2023). Based on this information and previous scientific research, the study focused on the months between May and October.…”
Section: Figure 1 Study Areamentioning
confidence: 99%
“…The ambient temperature in Antalya in November was determined as 15 ℃ and based on the assumption that the water temperature was 30 ℃, the required collector heat load calculations were carried out for heating a swimming pool with solar energy [5]. The average wind speed value for Antalya province was taken as 𝑉 𝑜 2.3 m/s and relative humidity as 64% [6]. In addition, the 𝑃 𝑂 value was determined as 4.2 kPa and the 𝑃 𝐶 value was 3.84 kPa for 30 ℃ water temperature from Figure 1 [7].…”
Section: B Calculation Of Heating Load For Heating Pool Watermentioning
confidence: 99%